Extending the Metaverse: Hyper-Connected Smart Environments with Mixed Reality and the Internet of Things - Guan, Jie; Morris, Alexis; Irizawa, Jay (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
The metaverse, i.e., the collection of technologies that provide a virtual twin of the real world via mixed reality, internet of things, and others, is gaining prominence. However, the metaverse faces challenges as it grows toward mainstream adoption. Among these is the lack of strong connections between metaverse objects and traditional physical objects and environments, which leads to incon-sistencies for users within metaverse environments. To address this issue, this work explores the design and development of a framework for bridging the physical environment and the metaverse through the use of internet-of-things objects and mixed reality designs. The contributions of this include: i) an architectural framework for ex-tending the metaverse, ii) design prototypes using the framework. Together, this exploration charts the course toward a more cohesive and hyper-connected metaverse smart environment.